Impact of patient education videos on genetic counseling outcomes after exome sequencing. Issue 1 (January 2020) - Hernan, Rebecca; Cho, Megan T.; Wilson, Ashley L.; Ahimaz, Priyanka; Au, Catherine; Berger, Sara M.; Guzman, Edwin; Primiano, Michelle; Shaw, Jessica E.; Ross, Meredith; Tabanfar, Leyla; Chilton, Ilana; et al.
Highlights: Parents reported that educational videos were helpful in understanding genetics. Satisfaction with genetic counseling was equivalent for standard care and videos. Genetic counselors did not report significant differences between the two groups. Creating effective and efficient educational tools is challenging. Standardized measures of educational tools need to be developed and validated. Abstract: Objective: Growing use of clinical exome sequencing (CES) has led to an increased burden of genomic education. Self-guided educational tools can minimize the educational burden for genetic counselors (GCs). The effectiveness of these tools must be evaluated. Methods: Parents of patients offered CES were randomized to watch educational videos before their visit or to receive routine care. Parents and GCs were surveyed about their experiences following the sessions. The responses of the video (n = 102) and no-video (n = 105) groups were compared. Results: GCs reported no significant differences between parents in the video and no-video groups on genetics knowledge or CES knowledge. In contrast, parents' scores on genetics knowledge questions were lower in the video than no-video group (p = 0.007). Most parents reported the videos were informative, and the groups did not differ in satisfaction with GCs or decisions to have CES. Conclusion: GCs and parents perceived the videos to be beneficial. However, lower scores on genetics knowledge questions highlight the need for careful development of educational tools. Practice implications: Educational tools should be developed and assessed for effectiveness with the input of all stakeholders before widespread implementation. Better measures of the effectiveness of these educational tools are needed.